Modifiable risk factors of hypertension: A hospital‐based case–control study from Kerala, India - Zarin Pilakkadavath and Muhammed Shaffi (J Family Med Prim Care, 2016)
Introduction: Hypertension is a major cause of cardiovascular morbidity and mortality in Kerala. Excess dietary salt, low dietary potassium, overweight and obesity, physical inactivity, excess alcohol, smoking, socioeconomic status, psychosocial stressors, and diabetes are considered as modifiable risk factors for hypertension. Objectives: To estimate and compare the distribution of modifiable risk factors among hypertensive (cases) and nonhypertensive (controls) patients and to estimate the effect relationship of risk factors. Materials and Methods: Age‐ and sex‐matched case–control study was conducted in a tertiary care hospital in Kerala using a pretested interviewer‐administered structured questionnaire based on the WHO STEPS instrument for chronic disease risk factor surveillance. Bivariate and multiple logistic regression analyses were done. Results: A total of 296 subjects were included in the study. The mean age of study sample was 50.13 years. All modifiable risk factors studied vis‐à‐vis obesity, lack of physical activity, inadequate fruits and vegetable intake, diabetes, smoking, and alcohol use were significantly different in proportion among cases and controls. Obesity, lack of physical activity, smoking, and diabetes were found to be significant risk factors for hypertension after adjusting for other risk factors. Conclusion: Hypertension is strongly driven by a set of modifiable risk factors. Massive public awareness campaign targeting risk factors is essential in controlling hypertension in Kerala, especially focusing on physical exercise and control of diabetes, obesity, and on quitting smoking.